Anthrax outbreak: exploring its biological agents and public health implications - Ogunleye, Seto C.; Olorunshola, Mercy M.; Fasina, Kolapo A.; Aborode, Abdullahi T.; Akinsulie, Olalekan C.; Amoo, Abimbola; Olatoye, Boluwatife J.; Bakare, Akeem; Lawal, Mariam A.; Adekanye, Oluwabori; Chinyere, Ezemba C. (Frontiers in Tropical Diseases, 2024)
The (re)emergence of several infectious zoonoses underlines the need for the re-evaluation of the transmission patterns and key players responsible for effective inter-species transfer of diseases. Anthrax is caused by Bacillus anthracis, a zoonotic rod-shaped, Gram-positive, spore-forming bacterium that is highly fatal to both human and animal populations. B. anthracis is widespread across several regions of the world, including Africa, Asia, southern Europe, North and South America, and Australia, and it has a remarkably high attendant impact on the sustainability and profitability of livestock. The current trend in the global distribution of anthrax necessitates an urgent contextual understanding of the key drivers of the spread of B. anthracis in different parts of the world toward the end goal of an anthrax-free world. The understanding of the drivers is integral for the development of control and preventive measures, and also the development of agents such as therapeutics and vaccines against B. anthracis. This review presents a holistic description of the transmission pattern and epidemiology of B. anthracis, and updates on the diagnostic techniques and approaches available for the detection of B. anthracis. In addition, this review highlights plausible prevention and control strategies for the bacterium. This review further underscores the need for participatory epidemiology, hygiene, and safety protocols, the establishment of comprehensive surveillance systems, and global collaborative efforts toward vaccine development as critical steps in controlling anthrax.